In Silico Study of Acetogenin Compounds from Soursop (Annona muricata) Leaves as Sodium-Glucose Cotransporter-2 (SGLT2) Inhibitors: Studi In Silico Senyawa Acetogenin dari Daun Sirsak (Annona muricata) Sebagai Inhibitor Sodium-Glucose Cotransporter-2 (SGLT2) - Tedjo, Aryo (Jurnal Tumbuhan Obat Indonesia, 2024)
Acetogenin derived from soursop (Annona muricata) leaves are known to have antidiabetic and anticancer activities. Nevertheless, there has been no study related to the compounds found in A. muricata leaves, such as acetogenin, as SGLT2 inhibitors. This research aims to investigate the activity of acetogenin compounds as SGLT2 inhibitors while maintaining low selectivity against SGLT1 using molecular docking methods using Molegro Virtual Docker (MVD). Based on the Rerank score, five acetogenin compounds, namely muricin H, annonacin A, annopentocin B, murihexocin C, and corossolone, are predicted to be SGLT2 inhibitors with better selectivity compared to empagliflozin. Among these five compounds, muricin H and corossolone exhibit the most similarity in interaction with amino acid residues in the SGLT2 A-chain compared to empagliflozin. In silico ADMET analysis results indicate that both compounds have absorption, distribution, and metabolism capabilities, similar to empagliflozin. However, it should be noted that both compounds are more toxic, with muricin H predicted to have hepatotoxic properties.